The state of reading culture among secondary school students in Croatia: survey results - Andreja Zubac (Knjižnica)
Purpose: Reinforcement and development of reading culture of secondary school students through theoretical and research section of the paper. The concept of reading culture among students of secondary schools is connected with the path of the book. Methodology/approach: The research shows results of the national survey made in the Republic of Croatia among students of secondary schools. The instrument used was a questionnaire. The research was anonymous. The sample obtained is convenient. The number of respondents was 251. Results of the research were processed by the computer programme Statistical Package for Social Sciences (SPSS), by means of a descriptive statistics and they are presented in percentages. Results: According to the processed sample, the results of this research showed that almost 1/3 of the students in Croatia did not have a developed reading culture. However, 2/3 of the respondents read at least one book per month. The survey encompassed a smaller number of secondary school students only in Croatia, so the sample was not representative. The research has shown that information channels need to be improved in order for information and books to reach students, potential readers. Research limitations: Students’ indifference to solve a questionnaire resulting in a nonrepresentative sample. Originality/practical implications: The research is the starting point for new surveys on reading culture of secondary school students. In Croatia, there is a lack of national representative and comprehensive researches of this kind, so it is assumed that the results of the survey will provide new hypotheses for future researches.